Assessing the Impact of PVC Pipe Diameter on Compressive Strength and Cracking in Hollow Prism Concrete - Asnan, Muhammad Noor; Saputra, Sahrul Panji; Noor, Rusandi (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2023)
In order to enhance the utilization of concrete, it is necessary to explore the impact of PVC pipes incorporated into hollow prism concrete, focusing on their effects on compressive strength and cracking. PVC pipes are commonly employed as reinforcements within concrete structures to bolster their stability. This research delves into the consequences of varying pipe diameters and PVC pipes within hollow prism concrete. The experimental process entails utilizing concrete prisms with 100 x 100 x 300 mm³ dimensions, possessing a compressive strength of 25 MPa. Research outcomes reveal that pipe diameter directly influences compressive strength, where larger diameters are associated with reduced compressive strength. Including pipes in the concrete does not yield a substantial discrepancy in compressive strength. Concrete prisms with incorporated pipes exhibit a Columnar-type collapse, indicative of dominant compressive stress, whereas prisms without pipes undergo a Shear-type collapse, signifying a shift in stress distribution. It emphasizes the pivotal role of reinforcements like PVC pipes in upholding the structural integrity of concrete, thereby mitigating potential damage.In order to enhance the utilization of concrete, it is necessary to explore the impact of PVC pipes incorporated into hollow prism concrete, focusing on their effects on compressive strength and cracking. PVC pipes are commonly employed as reinforcements within concrete structures to bolster their stability. This research delves into the consequences of varying pipe diameters and PVC pipes within hollow prism concrete. The experimental process entails utilizing concrete prisms with 100 x 100 x 300 mm³ dimensions, possessing a compressive strength of 25 MPa. Research outcomes reveal that pipe diameter directly influences compressive strength, where larger diameters are associated with reduced compressive strength. Including pipes in the concrete does not yield a substantial discrepancy in compressive strength. Concrete prisms with incorporated pipes exhibit a Columnar-type collapse, indicative of dominant compressive stress, whereas prisms without pipes undergo a Shear-type collapse, signifying a shift in stress distribution. It emphasizes the pivotal role of reinforcements like PVC pipes in upholding the structural integrity of concrete, thereby mitigating potential damage.